The strengthening mechanism synergy of heat-treated 3D printed Al-Sc alloy - Kuo, Che-Nan; Peng, Po-Chun (Virtual and physical prototyping, 2023)
According to the material nature, aluminium alloys are widely applied in aerospace, construction and automotive applications due to their characteristics, such as lightweight, good formability and good corrosion resistance. Among the aluminium alloys, scalmalloy (Al-4.49Mg-0.71Sc-0.51Mn-0.27Zr-0.07Fe-0.03Si alloy) was developed to overcome the hot crack issue during the laser powder bed fusion (LPBF) process. Hence, the degree of lightweight can be further improved by introducing this high-specific strength material with a structure of the lightweight design. However, the strengthening mechanism of the heat-treated 3D printed scalmalloy has not been sufficiently explored. In this study, the synergistic effect of the strengthening mechanisms is explored through detailed microstructure analysis. The grain size, size and spacing of the precipitate and coherent phase contribute to the strengthening of scalmalloy. Through the observation of the microstructure feature, the theoretical strength of the heat-treated 3D printed scalmalloy can thus be calculated by three strengthening mechanisms and match the experimental results perfectly.